2018
DOI: 10.1148/radiol.2017170673
|View full text |Cite
|
Sign up to set email alerts
|

Detection Rates of Ductal Carcinoma in Situ with Biennial Digital Mammography Screening: Radiologic Findings Support Pathologic Model of Tumor Progression

Abstract: Purpose To compare detection rates of ductal carcinoma in situ (DCIS), classified according to nuclear grade, between the prevalence round (baseline screening) and two subsequent screening rounds of a population-based digital mammography screening program, to assess differences over time. Materials and Methods The cancer registry provided data for 1970 graded pure DCIS cases from 16 screening regions of the prevalence round (baseline screening, from 2005 to 2008), first subsequent round, and second subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
3
5
0
Order By: Relevance
“…Von Luijt et al 12 analyzed a cohort of 4232 women with screen detected DCIS: most DCIS were intermediate (32%) and high grade (52%). Similar data were obtained by Weigel et al 13 confirming the importance of screening in detecting high grade DCIS. Furthermore, Weigel et al 13 demonstrated that the incidence of high-grade DCIS remained high even in the second and subsequent screening rounds.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Von Luijt et al 12 analyzed a cohort of 4232 women with screen detected DCIS: most DCIS were intermediate (32%) and high grade (52%). Similar data were obtained by Weigel et al 13 confirming the importance of screening in detecting high grade DCIS. Furthermore, Weigel et al 13 demonstrated that the incidence of high-grade DCIS remained high even in the second and subsequent screening rounds.…”
Section: Introductionsupporting
confidence: 87%
“…Similar data were obtained by Weigel et al 13 confirming the importance of screening in detecting high grade DCIS. Furthermore, Weigel et al 13 demonstrated that the incidence of high-grade DCIS remained high even in the second and subsequent screening rounds.…”
Section: Introductionsupporting
confidence: 87%
“…As to limitations of the study, we point out that ductal carcinoma in situ is not included in this model. DCIS accounts for nearly 20% of the DM screen-detected tumours in the Dutch population and similar proportions are detected in other population screening programs [18,46]. However, previous studies have shown that DBT plus DM can increase invasive CDR without preferentially increasing the proportion of DCIS compared to DM alone [47].…”
Section: Discussionmentioning
confidence: 83%
“…In the US National Cancer Database, delay in the surgical treatment of DCIS up to one year after diagnosis was an independent predictor of finding invasive cancer at surgical excision [9]. These effects are probably driven predominantly by the behaviour of high grade DCIS which has a higher rate of proliferation than lower grade disease [10,11].…”
Section: Introductionmentioning
confidence: 99%